Analisa Stakeholder Dalam Penerapan Skema Land Value Capture di Kawasan Perdagangan Bebas Dompak, Tanjung Pinang - Alwan, Muhammad Hafizh; Pradoto, Wisnu (Teknik PWK (Perencanaan Wilayah Kota), 2024)
The purpose of this study is to identify the condition of stakeholders in the Dompak Free Trade Zone who have their own institutional patterns and government ways of working that have the opportunity to support the implementation of Land Value Capture. This study was conducted with a qualitative approach through descriptive analysis, namely reviewing government regulatory documents relevant to the condition of the study area and then relating it to the application of Land Value Capture and take a questionnaire with stakeholders. Data collection techniques were carried out through literature study, document review, and questionary.The results of this study resulted in the grouping of each stakeholder into four categories namely key players, context setters, subjects, and crowds which were reviewed through six stages of stakeholder analysis. These results indicate a strong potential for implementing Land Value Capture where institutional regulations have supported the utilization of assets owned by local authorities. However, in its implementation, it still has to consider assets owned by local authorities and regulations that bind local government institutions to collaborate with each other in developing a land value capture-based Dompak Free Trade Zone.